A comparison of denitrifying bacterial community structures and abundance in acidic soils between natural forest and re-vegetated forest of Nanling Nature Reserve in southern China. (1st August 2017) - Meng, Han; Wu, Ruonan; Wang, Yong-Feng; Gu, Ji-Dong
Abstract: Denitrification plays a key role in converting reactive nitrogen species to dinitrogen gas back into the atmosphere to maintain the equilibrium of nitrogen cycling in ecosystems. In this study, functional genes of nirK and nosZ were used to detect the community structure and abundance of denitrifying microorganisms in acidic forest soils in southern China. Three sets of factors were considered for a comparison among 5 forests, including forest types (natural vs. re-vegetated), depths (surface layer vs. lower layer) and seasons (winter vs. summer). The community of nirK gene detected from these acidic forest soils was closely related to Proteobacteria especially α-Proteobacteria and uncultured soil sequences, while that of nosZ gene was affiliated with the α-, β- and γ-Proteobacteria . Higher diversity of denitrifiers was observed in re-vegetated forest soils than natural ones. Not only the community but also the abundance showed significant differences between forest types as well as depths. The abundance of denitrifiers ranged from 10 5 to 10 7 gene copies g −1 dry soil in this study. For nirK gene, the abundance was much higher in the lower layer than surface layer in both forest types, and the differences between winter and summer in natural forest soils were higher than those in re-vegetated forest soils. The abundance of nosZ and nirK genes showed a similar trend in natural forest, but the former was higher in matured forest than re-vegetated forest. This study provided a direct comparison on community composition and abundance of denitrifying bacteria in natural and re-vegetated acidic forest soils to allow further assessment of the nitrogen cycling. Graphical abstract: Highlights: Higher diversity of denitrifiers in re-vegetated than the natural forest soils. Acidic forest soils contain α-Proteobacteria and uncultured denitrifying bacteria by nirK gene. α-, β- and γ-Proteobacteria were detected by nosZ gene. nirK gene was highest in re-vegetated young forests in winter.